2020
DOI: 10.1007/s42452-020-03311-y
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigations to analyze the micro-hole drilling process in spark-assisted chemical engraving (SACE)

Abstract: With the increased utilization of glass in micro-electromechanical systems (MEMS) applications, need is generated to produce micro-features on glass with excellent surface quality, i.e., better hole circularity and less thermal cracks. Sparkassisted chemical engraving (SACE) has proven to be an emerging and reliable technology for micro-machining of glass that includes local joule heating of the work material for its removal. However, some problems need to be covered in the micro-hole drilling process such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…17 In the case of parabolic heat flux, the shape of the crater is shown in Figure 5(b), which has an approximate similar nature to the crater formed that of Gaussian heat flux. Similar nature of the crater is also obtained by considering cylindrical tools for the creation of the micro-holes at 25 wt% and 45 V. 28 As discussed, the nature of the crater depends on the temperature distribution within the substrate for various applied heat fluxes and types of tool electrodes used for sparking in the ECDM process.…”
Section: Comparison Of Crater Shape Forms With the Different Flux Pro...supporting
confidence: 55%
“…17 In the case of parabolic heat flux, the shape of the crater is shown in Figure 5(b), which has an approximate similar nature to the crater formed that of Gaussian heat flux. Similar nature of the crater is also obtained by considering cylindrical tools for the creation of the micro-holes at 25 wt% and 45 V. 28 As discussed, the nature of the crater depends on the temperature distribution within the substrate for various applied heat fluxes and types of tool electrodes used for sparking in the ECDM process.…”
Section: Comparison Of Crater Shape Forms With the Different Flux Pro...supporting
confidence: 55%
“…The optimum control of the voltage is very crucial since very high voltage values lead to thermal cracks while a minimum value is required to initiate the sparks [59,60]. Higher voltage values result in more thermal cracks at the microhole edge as reported by Rajput et al [54] in Fig. 8.…”
Section: Electricalmentioning
confidence: 88%
“…The HAZ produced is equivalent to the diameter of the discharge spot. Several authors have demonstrated the applications of the finite element modeling (FEM) for analyzing the ECDM process using single spark phenomena [52][53][54][55]. A summarized report on the development of the FEM-based thermal model in ECDM is shown in Fig.…”
Section: Phenomena Of Gas Film Stability and Sparkmentioning
confidence: 99%
“…Many studies reported that thermal heating is solely responsible for material while many suggested that chemical etching action also plays a crucial role in the removal of material. 12 Wuthrich et al 13 systematically characterized the gravity tool feed control for drilling micro-holes on glass materials. Maillard et al 14 successfully produced holes on glasswork materials and concluded that micro-holes geometrical features depend upon input variables.…”
Section: Introductionmentioning
confidence: 99%